Flue-cured tobacco intercropping with insectary floral plants improves rhizosphere soil microbial communities and chemical properties of flue-cured tobacco - Jin Zhong; Wenze Pan; Shenglan Jiang; Yanxia Hu; Guangyuan Yang; Ke Zhang; Zhenyuan Xia; Bin Chen (BMC Microbiology)
Abstract Background Continuous cropping of the same crop leads to land degradation. This is also called the continuous-cropping obstacle. Currently, intercropping tobacco with other crops can serve as an effective strategy to alleviate continuous cropping obstacles. Results In this study, tobacco K326 and insectary floral plants were used as materials, and seven treatments of tobacco monoculture (CK), tobacco intercropped with Tagetes erecta, Vicia villosa, Fagopyrum esculentum, Lobularia maritima, Trifolium repens, and Argyranthemum frutescens respectively, were set up to study their effects on rhizosphere soil chemical properties and composition and structure of rhizosphere soil microbial community of tobacco. The 16 S rRNA gene and ITS amplicons were sequenced using Illumina high-throughput sequencing. tobacco/insectary floral plants intercropping can influence rhizosphere soil chemical properties, which also change rhizosphere microbial communities. The CK and treatment groups tobacco rhizosphere soil microorganisms had significantly different genera, such as tobacco intercropping with T. repens and A. frutescens significantly increased the number of Fusarium and intercropping T. erecta, V. villosa, L. maritima, T. repens, and A. frutescens significantly increased the number of Sphingomonas and unknown Gemmatimonadaceae. Additionally, intercropping T. erecta, V. villosa and L. maritima changed the rhizosphere fungal and bacteria community and composition of tobacco and the positive correlation between tobacco rhizosphere the genera of fungi and bacterial were greater than CK. The pathway of the carbohydrate metabolism, amino acid metabolism, and energy metabolism in rhizosphere bacteria were significantly decreased after continuous cropping. Fungal symbiotic trophic and saprophytic trophic were significantly increased after intercropping V. villosa, L. maritima and plant pathogen and animal pathogen were increased after intercropping T. repens and A. frutescens. Additionally, bacterial and fungal communities significantly correlated with soil chemical properties, respectively. Conclusion This study reveals that intercropping tobacco with insectary floral plants, particularly T. erecta, V. villosa, L. maritima and A. frutescens significantly affects soil chemical properties and alters rhizosphere microbial communities, increasing the abundance of certain microbial genera. Additionally, intercropping enhances pathways related to carbohydrate, amino acid, and energy metabolism in rhizosphere bacteria. These findings suggest that intercropping could provide a promising strategy to overcome challenges associated with continuous tobacco cropping by regulating the rhizosphere environment.